The Contest of Moral Values and Human Rights in the Formulation of Criminal Offenses inbthe National Criminal Code - Amir Minabari (PT. Anagata Sembagi Education, 2026)
The establishment of the National Criminal Code through Law Number 1 of 2023 reflects the state's efforts to harmonize the criminal law system with the moral values that live in Indonesian society. The process of codifying criminal norms cannot be separated from the moral plurality that comes from religion, customs, and culture, which are often used as a reference for criminalization. However, differences in the acceptance of moral values pose a challenge to legitimacy when criminal norms are generally binding. Law Number 1 of 2023 shows the tendency to use morality as a basis for criminalization, which has the potential to expand delicacies, create legal uncertainty, and risk discrimination against minority groups. The protection of human rights is the main parameter, especially related to the right to privacy, the principle of non-discrimination, and the limits of state intervention. The harmonization between public morality, the protection of individual rights, and the principle of the rule of law still faces normative and structural tensions. Overcriminalization can weaken the selective power of criminal law and burden the justice system. Critical and normative evaluation is needed to ensure that criminal law functions as an instrument of justice and protection of rights, not just a tool of moral affirmation. Normative juridical research shows the need for a balance between moral values, social interests, and human rights in order for the National Criminal Code to have strong juridical, sociological, and philosophical legitimacy.